Can biomass distribution across trophic levels predict trophic cascades?. (13th December 2020) - Galiana, Núria; Arnoldi, Jean‐François; Barbier, Matthieu; Acloque, Amandine; de Mazancourt, Claire; Loreau, Michel
Abstract: The biomass distribution across trophic levels (biomass pyramid) and cascading responses to perturbations (trophic cascades) are archetypal representatives of the interconnected set of static and dynamical properties of food chains. A vast literature has explored their respective ecological drivers, sometimes generating correlations between them. Here we instead reveal a fundamental connection: both pyramids and cascades reflect the dynamical sensitivity of the food chain to changes in species intrinsic rates. We deduce a direct relationship between cascades and pyramids, modulated by what we call trophic dissipation – a synthetic concept that encodes the contribution of top‐down propagation of consumer losses in the biomass pyramid. Predictable across‐ecosystem patterns emerge when systems are in similar regimes of trophic dissipation. Data from 31 aquatic mesocosm experiments demonstrate how our approach can reveal the causal mechanisms linking trophic cascades and biomass distributions, thus providing a road map to deduce reliable predictions from empirical patterns. Abstract : Biomass pyramids and trophic cascades, are archetypal representatives of the interconnected set of static and dynamical properties of food chains. We reveal a fundamental connection between them: both reflect the dynamical sensitivity of the food chain to changes in species intrinsic rates. A synthetic concept that encodes the contribution of top‐down propagation of consumer losses in the biomass pyramid regulates the relationship between pyramids and cascades. Thus, our framework can reveal the causal mechanisms linking trophic cascades and biomass pyramids, providing a road map to deduce reliable predictions from empirical patterns.